Exploration of Ethnomathematics in Betawi Batik Motifs for Teaching Plane Geometry - Widiyasari, Ririn; Wiratno, Kartika Nur Syahbani (Jurnal Pendidikan Matematika, 2025)
Batik is one of Indonesia's cultural heritages that must be preserved. Batik has different characteristics and philosophies in each region, one of which is Betawi batik. Betawi batik has various characteristics and philosophies in each motif which, if examined more deeply, are related to flat shapes or mathematical concepts. The relationship between culture and mathematics is also known as ethnomathematics. The purpose of this research is to explore the concept of flat shapes in Betawi batik motifs. The research method used is a qualitative method with an ethnographic approach. This research uses human instruments, namely the researchers themselves, where everything that happens in the field will be recorded by researchers using exploration and observation guidelines, digging and analyzing all documents found and presenting them in the research results. The result of this study is that in Betawi batik motifs there is a concept in the form of flat shapes. The flat shapes found in this type of Betawi batik motif are triangles, squares, rectangles, rhombuses, kites, trapezoids, and circles. The results of this study are related to the process of learning mathematics in schools and can be used as learning materials at the primary and secondary school levels.